Chlorophyll Content of Jabon Leaves (Anthocephalus cadamba [Roxb] Miq.) in the Sungai Nyalo, Pesisir Selatan and Lubuk Alung, Padang Pariaman - Vauzia Vauzia; Resti Fevria; Yovella Trisna Wijaya (Bioscience, 2019)
Jabon (Anthocephalus cadamba [Roxb] Miq.) is one type of tree that has a high prospect for industrial plantations and reforestation in Indonesia, due to its very fast growth and relatively easy silvicultural treatment. The growth of a plant is strongly influenced by photosynthesis. The process of photosynthesis can take place because of the presence of pigments called chlorophyll. The formation of chlorophyll is influenced by environmental factors. Therefore, studies have been carried out on the chlorophyll content of Jabon leaves in different locations. This research was conducted from March to May 2019. The samples came from the Sungai Nyalo, Pesisir Selatan, and Lubuk Alung, Padang Pariaman. While the chlorophyll content of Jabon leaves was tested at the Laboratory of Plant Physiology, Department of Biology, FMIPA UNP. This research is a descriptive study that was analyzed by the T test at a significant level of 5%. The results showed that there were differences in the chlorophyll content of Jabon leaves in the Sungai Nyalo, Pesisir Selatan with value 44,26 (mg/g) and Lubuk Alung, Padang Pariaman with value 19,45 (mg/g).